ANALISIS FAKTOR RISIKO DENGAN KEJADIAN ISPA ANAK DI PUSKESMAS KECAMATAN PASAR REBO SAAT 6 BULAN PERTAMA PANDEMI COVID - 19 - Febyola Nur Fitriyani, (2021)
The prevalence period of ARI in 2013 in Indonesia was 25.0% in the five highest provinces and there was a decrease in 2018 which was about 16.2%. while at Pasar Rebo Primary Health Center in 2018 ARI was in first place at 23.8%. This study aimed to determine the factors associated with ARI's prevalence for children at Pasar Rebo Primary Health Center during the when the first 6 month exposed to the Covid-19 was the purpose of this study. The design analysis of this study is cross-sectional. The population in this study was a pediatric who came up with respiratory tract symptom with a sample count of 154 respondents and the sampling technique was consecutive sampling. The secondary data form was medical records, the results of the Chi-square test study showed that the age risk factor is P = 0.01 (OR 0.39 and CI 0.18-0.84), the gender factor is P = 0.2 and in nutritional status is P = 0.42. It concluded that age has an association with the incidence of ARI, with a higher risk of occurring in toddlers. Toddlers are prone to suffer from ARI, this is thought to be due to immunity in toddlers is still not perfect and the shape of the airway is narrower than the age above. In addition, bad environmental factors have the potential to cause ISPA.